Prasasti Tulang Er 198 Sanjaya - HB. Herry Santosa (Balai Arkeologi Yogyakarta, 1994)
The inscription is a source of written history which provides a lot of information about the structure of the bureaucracy, economy, topography, settlement and also about the problems of ancient Indonesian society and their activities. Based on the data collected, hundreds of inscriptions use the Caka year and only four inscriptions use the Sanjaya year. One of the inscriptions has Sanjaya year, namely the Tulang Er 198 Sanjaya inscription. The inscription which is now kept at the National Museum has not been discussed much. Basically, this inscription does not change the theory or reconstruction of existing history. However, the existence of this inscription can in fact complement existing historical writing. The Sanjaya year, is no longer only a complement to the dates that have been used in Indonesia, but is also evidence that during the reign of Balitung-Daksha there was a conflict within the palace in order to fight for the royal throne. This paper also contains a transcription of the Tulang Er 198 Sanjaya inscription.